IMF Research Bulletin, September 2009. (IMF Research Bulletin; IMF Research Bulletin, 2009)
The Q and A in this issue features seven questions about policy options for emerging market countries (by Marcos Chamon, Chris Crowe, and Jun Il Kim); research summaries on 'Does Trade and Financial Globalization Cause Income Inequality?' (by Chris Papageorgiou) and 'The Current Account of Oil-Exporting Countries (by Irineu E. de Carvalho Filho); an article on the launch of the IMF's new research journal, IMF Economic Review, and the contents of the upcoming IMF Staff Papers, which the new the new journal will succeed in 2010; an article on the upcoming Tenth Annual Jacques Polak Research Conference; a listing of visiting scholars at the IMF during July-September 2009; and listings of recent IMF Working Papers and Staff Position Notes.